2014
DOI: 10.1177/003335491412900505
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Childhood Influenza Vaccination Coverage—U.S., 2004–2012

Abstract: Although influenza vaccination coverage among children continued to increase, by the 2011-2012 influenza season, only slightly less than half of U.S. children were vaccinated against influenza. Much improvement is needed to ensure all children aged ≥ 6 months are vaccinated annually against influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 11 publications
0
33
1
Order By: Relevance
“…50 -52, 58, 68 -70 Although we found no disparities between black and white children, we did observe higher uptake in Asian, Hispanic, and other/multiracial children. There were no significant racial/ethnic disparities nationally among children in most recent influenza seasons, 69 although higher uptake among Asian children has been observed. 70 Generally, higher parental education is associated with higher influenza vaccine uptake in children.…”
Section: Discussionmentioning
confidence: 86%
“…50 -52, 58, 68 -70 Although we found no disparities between black and white children, we did observe higher uptake in Asian, Hispanic, and other/multiracial children. There were no significant racial/ethnic disparities nationally among children in most recent influenza seasons, 69 although higher uptake among Asian children has been observed. 70 Generally, higher parental education is associated with higher influenza vaccine uptake in children.…”
Section: Discussionmentioning
confidence: 86%
“…This is to be expected because previously published reports of coverage with at least 1 dose of influenza vaccination have shown increases during this time. 19,23 Despite the increase, the majority of children 6 to 23 months in the United States were not fully vaccinated against influenza.…”
Section: Discussionmentioning
confidence: 99%
“…10 To our knowledge, Brim et al 11 was the first to provide national population-level estimates of influenza vaccination coverage among children with asthma, examining the 2004–2005 influenza season and finding that the influenza vaccination rate was 29.0% among children 2 to 17 years of age with asthma and 10.3% among those without asthma. Although recent research has shown that coverage has increased since then among children with and without chronic conditions, 12 influenza vaccination among children with asthma specifically has not been evaluated since the 2004–2005 season, and trends over time are unknown. 11 In addition, the percentage of children with asthma who receive early influenza vaccination has not been examined.…”
mentioning
confidence: 99%